(untitled) (Laisvalaikio tyrimai, 2020)
Reinterpretation of the Japanese constitution has actual and potential impact on International Relations in the wider North East Asian region. Most research had been dedicated to the issue of Article 9, which limits Japan’s military capability. The current study is going analyse Article 20 of Japan’s fundamental legal document, which also has an influence on Japan’s role on the international stage. Article 20 de-jure establishes that Japan is a secular state. However, with the current global trend of desecularisation, it is important to consider to what extent Japan is actually secular. Keywords: secularism, Japan, Korea, China, Buzan